POST PENAL ASSISTANCE OF EX-PRISONERS – the case of the Republic of Macedonia – - Gruevska Drakulevski, Aleksandra (Iustinianus Primus Law Review, 2011)
The author of the paper deals with the issue of post penal assistance of ex-prisoners. The author gives a review of the best practicies of implementation of the post penal assistance, namely the Anglo-Saxon countries. The paper analyses the application of the post penal assistance of ex-prisoners in the Republic of Macedonia. Post penal assistance is seen as an extended treatment of the convict. This form of treatment is an element of re-socialization as a continuous process aimed at successful engagement of the ex-prisoner in the lawful life. Post penal assistance can be internal, that is encouragement and advice of the convicts to solve their own problems they would face immediately after release from the penal institution. On the other hand is the external assistance that is manifested through various forms, such as: providing temporary accommodation and nutrition, providing necessary treatment, selection of a new environment in which the convicted person will live, assisting in arranging family situation, finding suitable employment, enabling to finish school, providing financial assistance to cover the most necessary needs, etc. External post penal assistance is the real after care of ex-prisoners. Post penal assistance as a form of treatment provides achievement of the principles of humanity in the execution of criminal sanctions. Measures taken by the institutions and bodies responsible for post penal assistance should be in accordance with the needs of prisoners.
Keywords: after-care, convict, ex-prisoner, help, post penal assistance, prison, reintegration, rehabilitation, re-socialization